Primary necrotizing fasciitis of the breast. Case series with 5 patients - Yilmaz, Kerim Bora; Saydam, Mehmet; Akinci, Melih; Akkoca, Muzaffer; Arikok, Ata Turker; Guler, Sumeyra; Tokgöz, Serhat; Gulcelik, Mehmet Ali (The Journal of Infection in Developing Countries, 2022)
Necrotizing fasciitis (NF) is an aggressive, necrotic, life-threatening infection of the soft tissues. The delay on treatment is generally accompanied by almost 90 % lethality according to the development of septic shock and its associated complications. Primary Necrotizing Fasciitis of the Breast (PNFB) is seen extremely rare. To date, breast necrotizing fasciitis have been reported only as a limited number of case reports in the literature. PNFB is commonly misdiagnosed as cellulitis, mastitis, abscess or inflammatory breast cancer. Although PNFB is a very rapid and aggressive disease, which can be fatal. Delayed cases were unfortunately resulted in mortality due to several consequential reasons. Therefore, careful and detailed evaluation of all cases irrespective of age, especially those with risk factors and comorbidities, could be life saving in respect of early diagnosis and timely treatment. Our aim is to to present the analysis and treatment modalities of five primarily seen PFNB, in this case series.